Characterization of a "Smart" Hybrid Varnish Electrospun Nylon Benzotriazole Copper Corrosion Protection Coating. (11th December 2012) - Menchaca, C.; Castañeda, I.; Soto-Quintero, A.; Guardián, R.; Cruz, R.; García-Sánchez, M. A.; Uruchurtu, J.
Abstract : This work presents the electrochemical evaluation of a proposed copper corrosion protection hybrid coating acting as a smart corrosion protection system. This consists of an alkyd varnish, painted over electrospun nylon fibers acting as a secondary diffusion barrier and also as a benzotriazole (BTAH) inhibitor nanocontainer. Submicron diameter electrospun nylon 6-6 fiber nanocontainers were prepared from a polymeric solution containing BTAH at different concentrations, and Cu samples were coated with the electrospun fibers and painted over with an alkyd varnish by the drop method. Functional groups in fibers were determined through FTIR spectroscopy. Optical and SEM microscopies were used to characterize the nanocontainer fibers. Samples were evaluated using electrochemical impedance and noise, during six weeks of immersion, in a chloride-ammonium sulfate solution. Excellent response was obtained for the smart inhibitor coating system. For long periods of immersion good corrosion protection performance was observed. The results presented demonstrate the good barrier properties of the hybrid coating, obstructing the diffusion of aggressive species, through the electrospun structure. Furthermore the nanocontainer functionality to store and liberate the corrosion inhibitor, only when it is needed, was also proved.